Estudio de la Ploidía en Plukenetia Volubilis L, (Sacha Inchi) - Borbor Torres, Manuel Alejandro (2010)
We evaluated 10 accessions of Plukenetia volubilis L. "Sacha Inchi" from the National Collection of Research Branch, Genetic Resources and Biotechnology - SUDIRGEB Experimental Station "El Porvenir" - INIA and two wild ecotypes Apangurayacu (Plukenetia volubilis L.) and Lamas (Plukenetia huayllabambana) from the Province Lamas, San Martin Región in Perú; in order to determine the ploidy levels, time of collection of root tips, standardize the methodology for counting chromosomes and determine the number of chromosomes in Plukenetia volubilis L. and the kind Plukenetia huayllabambana. Established that the most appropriate collection of root tips is 12 hours with an MI of 13%. The number of chromosomes was performed using the prefixation: in 1% colchicine at 4 ° C for 8 hours, or 8-hydroxyquinoline at 0.0005M and 0.001M at 4 ° C for 6 and 8 hours respectively, or in distilled water chilled at 4 ° C for 8 hours, then was fixed in solution Carnoy 3:1 for 24 h at 4 ° C, then followed by hydrolysis in 1 N hydrochloric acid at 60 ° C for 8 to 12 minutes and finally stained in aceto orcein 2% for 24 hours at 4 ° C. According to statistical analysis using fashion, it was determined that the species Plukenetia volubilis L. and have 56 chromosomes Plukenetia huayllabambana being Heptaploides with a basic number x = 8, also registering other common chromosome numbers 42, 44, 48, 52, 54, 58, 62 and less frequently found in cells 64, 72, 76, 82, 86, 90, 96 and 101 chromosomes. These variations of chromosome number may be because alelopoliploides species are found in the domestication process and / or adaptation, crossing each other for their survival.